Addressing seed security in disaster response - linking relief with development - Sperling, L.; Remington, T.; Haugen, J.M.; Nagoda, S (International Center for Tropical Agriculture, 2004)
This volume contains eight case studies managed by CIAT, CRS, and CARE Norway in a project entitled, Assisting disaster-affected and chronically stressed communities in East, Central and Southern Africa: Focus on small farmer systems. The case studies were undertaken to evaluate various forms of emergency seed aid and to couple these with analyses of the broader seed and crop systems. The objectives were to understand if and how vulnerable farmers are being helped by the kinds of assistance they receive —and how to move forward on improving practice.